EXAMINING THE INTENTION TO BUY ELECTRIC VEHICLES IN INDONESIA THROUGH TRUST, SECURITY, QUALITY, PERCEIVED USEFULNESS, AND ANTICIPATED REGRET - Andina Fasha; Robben Robben; Rizni Aulia Qadri; Devina Wistiasari (Journal of Global Business and Management Review, 2026)
The development of electric vehicles (EVs) in Indonesia is increasing, in line with the government's commitment to encouraging the transition to environmentally friendly transportation. However, the adoption rate of electric vehicles still faces various challenges that prevent people from having optimal purchase intentions. This study aims to analyze the influence of security, quality, perceived usefulness, and anticipated regret on trust and its impact on intention to buy electric vehicles in Indonesia. Trust is positioned as a mediating variable that bridges the relationship between independent variables and electric vehicle purchase intentions. This study uses a quantitative approach, employing a survey of 207 Indonesian respondents domiciled in Batam and possessing knowledge of or exposure to electric vehicles. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS 4. The results show that Trust has a strong positive effect on the intention to buy electric vehicles (β = 0.635) and significantly mediates the effects of all four antecedent variables on purchase intention. The findings provide a theoretical contribution to the development of consumer behavior literature and technology adoption literature and offer practical implications for electric vehicle manufacturers and the government in increasing public trust in electric vehicles.